Vibrational investigation on pharmaceutical activity of m-xylene-4-sulphonic acid by quantum computational and experimental support. Issue 1 (2nd January 2018) - Ramalingam, S.; Manzoor Ali, M.; George, Gene; Manthiri, A. Abbas; Periandy, S.
ABSTRACT: Detailed physical, chemical, thermal and circular vibrational investigations have been made on FT-IR, FT-Raman, NMR and UV–Visible spectra of m -xylene-4-sulphonic acid. The modification of the basic property of the base compound favoured by the asymmetric orientation of the charge levels among the atoms of the compound has been discussed in detail. The transitional pattern among the natural bond orbitals emphasized the inducement of the antibacterial and antifungal activity in the compound. Strong interpretations of the physical and chemical properties by intense observation using excitations between the electronic energy levels within the molecule have been carried out. The arrangement of the dipole moment of the bonds and the change of the resultant magnetic moment were observed from the average polarizability first-order diagonal hyperpolarizability. The receptor and inhibition property of the molecule were interpreted by the identification of reactive sites from the molecular electrostatic potential contour map. The chemical reaction continuity is keenly observed from thermodynamic analysis.